Utilizing Autoethnography Within a Course Structure to Support Developing Scholars. Issue 2 (May 2022) - Olszewski, Carol A.; Pontikos, Keli P.; Znamenak, Kyle A.; Selker, Matt L.; Paoletta, Toni M.; Coffman, Karrie A.; Hansman, Catherine A.
Developing scholars sometimes struggle to situate their own position in the research and to comprehend how that affects their attitudes and behaviors. They frequently experience imposter syndrome and feelings of inadequacy, which lead to anxiety toward the research and publication processes. This paper presents a method for incorporating collective autoethnography into a graduate course context, aiming to demystify such processes and to cultivate scholarly identity. The doctoral students in a graduate seminar agreed to journal following course meetings. Following completion of the course, the journal entries were compiled. This compilation was reviewed and reflected on by each member individually, and then the group met to collectively discuss the data. Since that initial study, the developing scholars have elected to continue their work together, with each member continuing to benefit from additional scholarship creation, continued peer mentorship, and a supportive group in which to continue to develop scholarly identity. Brief reflections by the authors illustrate their experiences. Through this collective work, the journals resulting in the autoethnography empowered students to understand their positionality and intersectionality, resulting in rich and layered autoethnographic accounts of learning. Through their interests in the jointly conducted project, students gained a sense of authority and position from which to analyze their growing knowledge and identities as scholars.